Development of two-phase flow microchannel heat sink applied to solar-tracking high-concentration photovoltaic thermal hybrid system. (1st December 2020) - Hong, Sihui; Zhang, Bohan; Dang, Chaobin; Hihara, Eiji
Abstract: To enhance the energy conversion efficiency of a concentration photovoltaic (CPV) system, a high-concentration photovoltaic thermal (HCPVT) hybrid system is proposed in this study. This system extends the functionality of the CPV from simply generating electricity to simultaneously providing electricity and heat. Thus, the utilization of the exhaust heat, which would otherwise be lost to the environment, could enhance the overall system efficiency and boost the economic value of the generated power output. However, in view of the significant influence of the operating temperature on the photovoltaic efficiency and longevity of the solar cells, an efficient cooling of the photovoltaic module during the solar-tracking process has become a great challenge to the development of HCPVT hybrid systems. In the present work, a radially expanding microchannel heat sink (REMHS) employing two-phase flow boiling is proposed to achieve the twin objectives of cooling the solar cells and generating steam from the recovered heat. The radially expanding microchannels are designed to facilitate a spontaneous vapor removal while alleviating flow maldistribution arising due to the changes in orientation of the device. By conducting flow boiling tests of deionized water, the heat transfer characteristics of the proposed REMHS under various orientation angles were investigated. The local heat transfer coefficient of the REMHS increased by 32%, as the orientation angle of the microchannels increased from 0° to 45°, and then remained steady with any further increase in the orientation angle. In addition, the heat transfer capability of the REMHS exhibited a strong dependence on the heat flux and was weakly correlated with the flow rate, which is typical of an evaporation liquid film heat transfer. Additionally, by conducting outdoor real-time sun tracking tests under a concentration ratio of 1070 suns, it was found that the proposed REMHS maintained a superior flow boiling performance under a high-concentration solar energy. The highest surface temperature on the cell surface remained below 110 ° C and the observed maximum temperature difference was below 5 ° C. Highlights: A two-phase flow cooling device for solar energy hybrid system was proposed. Reliability of radial microchannel heat sink against sun-tracking was verified. Heat transfer characteristics of radial microchannel heat sink were evaluated. Superior performance of radial microchannel heat sink was proven by experiments. Two-phase flow dynamics under orientations was analyzed with visualization.